2018
DOI: 10.1371/journal.pone.0205962
|View full text |Cite
|
Sign up to set email alerts
|

Associations of birth mode with cord blood cytokines, white blood cells, and newborn intestinal bifidobacteria

Abstract: The associations of Cesarean delivery with offspring metabolic and immune-mediated diseases are believed to derive from lack of mother-to-newborn transmission of specific microbes at birth. Bifidobacterium spp., in particular, has been hypothesized to play a health-promoting role, yet little is known about how delivery mode modifies colonization of the newborn by this group of microbes. The aim of this research was to examine the presence of Bifidobacterium in meconium and in the transitional stool, and to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Verbal aggression, intimidation, disrespectful behaviour and even sexual harassment can be seen as risk factors for emotional exhaustion and even burnout (Viotti et al, 2015). Lack of support for novice nurses in a demanding healthcare environment may lead to emotional distress (Chang, Chu, Liao, Chang, & Teng, 2018;Fleury, Grenier, Bamvita, & Farand, 2018) and job dissatisfaction (Adriaenssens, de Gucht, van der Doef, & Maes, 2011). Bacon (2017 showed that unexpected patient death as an existential event has a major impact on feelings of emotional distress, shock and failure in the nursing role.…”
Section: Discussionmentioning
confidence: 99%
“…Verbal aggression, intimidation, disrespectful behaviour and even sexual harassment can be seen as risk factors for emotional exhaustion and even burnout (Viotti et al, 2015). Lack of support for novice nurses in a demanding healthcare environment may lead to emotional distress (Chang, Chu, Liao, Chang, & Teng, 2018;Fleury, Grenier, Bamvita, & Farand, 2018) and job dissatisfaction (Adriaenssens, de Gucht, van der Doef, & Maes, 2011). Bacon (2017 showed that unexpected patient death as an existential event has a major impact on feelings of emotional distress, shock and failure in the nursing role.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated that dexmedetomidine combined with lumbar anesthesia resulted in decreased expression of IL-2 and TNF-α, and increased expression of IL-4 and IL-10 in maternal females after caesarean section and their neonates compared with those who had received lumbar anesthesia alone. Although caesarean section may influence the level of IL-2 and IL-4, no significant differences compared with pregnant women with normal delivery have been reported (32). In the present study, all participants received caesarean section; therefore, the changes of IL-2 and IL-4 are due to the different anesthetic treatments.…”
Section: Discussionmentioning
confidence: 50%
“…This finding might be related to the type of delivery. Most of the infants in CMPA group were born by Cesarean section, which has been related to lower Bifidobacterium content due, at least in part, to delayed initiation of breastfeeding [28]. Moreover, in this study fecal samples of CMPA infants were also characterized by a higher abundance of the genus Rothia and the families Lachnospiraceae, Peptostreptococcaceae and Eggerthellaceae.…”
Section: Discussionmentioning
confidence: 58%